Mia Mayhem and the super switcheroo - West, Kara; Hernandez, Leeza (New York : Little Simon, 2021)
After a weird storm, Mia's superpowers are transferred to her best friend, Eddie, and she gets to train him to use them at her secret school.
3.9
K-3
Keywords: Ability -- Juvenile fiction; Superheroes -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction; African Americans -- Juvenile fiction; Ability -- Fiction; Superheroes -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Schools -- Fiction; African Americans -- Fiction